THE INFLUENCE OF IMPULSIVE BUYING BEHAVIOR, SELF-CONTROL, LIFESTYLE, AND RELIGIOSITY ON PAYLATER USAGE IN GENERATION Z - Aisha Hanif; Nur Amiliyah Safara (Journal of Artificial Intelligence and Digital Economy, 2026)
Abstract. This study aims to analyze the influence of impulsive buying behavior, self-control, lifestyle, and religiosity on the use of paylater among Generation Z students at Muhammadiyah University of Sidoarjo. The research method employed a quantitative approach with a sample of 100 respondents determined using the Slovin formula and simple random sampling. Data were analyzed using multiple linear regression. The results indicate that impulsive buying behavior, self-control, and lifestyle have a positive and significant effect on paylater usage, while religiosity has a negative and significant effect. An R-squared value of 0.558 indicates that the independent variables explain 55.8% of the variation in paylater usage. Validity and reliability tests showed that all instruments are suitable for use. In conclusion, psychological factors and lifestyle predominantly influence paylater usage, while religiosity suppresses its use. The implications of this study are expected to serve as a basis for evaluating the use of digital financial services for both users and paylater service providers in Indonesia in the future.